The flavor bible : the essential guide to culinary creativity, based on the wisdom of America's most imaginative chefs - Page, Karen; Dornenburg, Andrew (New York : Little, Brown and Co., 2008)
A detailed reference on how to season ingredients to draw out the best possible flavors contains thousands of entries on how to combine flavors and make informed choices about herbs, spices, and other seasonings.
Flavor = taste + mouthfeel + aroma + "the X factor" : learning to recognize the language of food -- Great cooking = maximizing flavor + pleasure by tapping body + heart + mind + spirit : communicating via the language of food -- Flavor matchmaking : the charts.
Keywords: Cooking; Gastronomy; Cooking; Gastronomy; Cooking; Gastronomy; Cooking; Cookbooks; Cookbooks